Impact of Wheat Resistance Genes on Wheat Curl Mite Fitness and Wheat Streak Mosaic Dynamics Under Single and Mixed Infections - Saurabh Gautam; Kiran R. Gadhave (Viruses)
The wheat curl mite (WCM, Aceria tosichella Keifer), a complex of eriophyid mite species, transmits wheat streak mosaic virus (WSMV) and Triticum mosaic virus (TriMV), which in single or mixed infections cause wheat streak mosaic (WSM) disease—a major threat to wheat production across the U.S. Great Plains. Resistant wheat cultivars bearing Cmc3 and Cmc4 (targeting WCM), Wsm1 and Wsm2 (targeting WSMV), and Wsm1 (targeting TriMV) are widely used to manage this pest–pathogen complex. However, comprehensive studies investigating how these resistance mechanisms influence both vector biology and virus transmission remain scarce. To address this gap, we evaluated disease development and WCM fitness across nine wheat cultivars with differential resistance profiles under single and mixed infections of WSMV and TriMV. We found strong viral synergy in co-infected plants, with TriMV accumulation markedly enhanced during mixed infections, irrespective of host genotype. Symptom severity and virus titers (both WSMV and TriMV) were highest in the cultivars carrying Wsm2, suggesting a potential trade-off in resistance effectiveness under mixed infection pressure. While mite development time (egg to adult) was unaffected by host genotype or infection status, mite fecundity was significantly reduced on infected plants carrying Wsm1 or Wsm2, but not on those with Cmc3 and Cmc4. Notably, virus accumulation in mites was reduced on the cultivars with Cmc3 and Cmc4, correlating with virus titers in the host tissues. Our findings highlight the complex interplay between host resistance, virus dynamics, and vector performance. Cultivars harboring Cmc3 and Cmc4 may offer robust field-level protection by simultaneously suppressing mite reproduction and limiting virus accumulation in both plant and vector.